Association between Periodontal Status and Prognosis in Men with Prostatitis: A Cross-Sectional Clinical Study - Flores-Fraile, Javier; Comerón, Pablo Ortíz de Urbina; Molinero-Mourelle, Pedro; Fiorillo, Luca; Galletti, Cosimo; Roccuzzo, Andrea; Gómez, María Fernanda Lorenzo (European Journal of Dentistry, 2025)
Prostatitis is the most prevalent urological condition in young adult men and may progress to prostate cancer, representing a significant public health concern. A high prevalence of inflammatory prostate disorders exists without a clearly identifiable cause. This article aimed to investigate the potential association between periodontal status and prognosis in men diagnosed with prostatitis and to evaluate whether oral health influences urological treatment outcomes.A cross-sectional clinical study was conducted on 172 adult patients with prostatitis who provided written informed consent. Participants were assigned to two groups based on bleeding index (BI): Group A (GA, n = 84), BI >7%, and Group B (GB, n = 88), BI ≤7%. All subjects underwent comprehensive periodontal assessment and nonsurgical periodontal therapy, with follow-up at 30 and 120 days.At baseline, GA showed significantly greater probing depths on proximal surfaces and higher BI values than GB (p < 0.01). Posttreatment, BI improved significantly in both groups, although GA maintained higher residual bleeding (p = 0.002). Mean posttreatment prostate-specific antigen (PSA) levels did not differ significantly between groups; however, PSA decreases occurred more frequently in GB (61.5%) than in GA (28.6%, p = 0.039), while PSA increases were more common in GA (57.1% vs. 15.4%, p = 0.005). Overall, 29.4% of patients exhibited lower PSA levels after periodontal therapy.While no direct association was found between periodontal status and absolute posttreatment PSA values, healthier periodontal conditions were linked to more favorable PSA trends. These findings suggest that periodontal health may contribute to PSA stability in men with prostatitis. Larger, longitudinal studies are warranted to clarify potential mechanistic links between oral and prostatic inflammation.
Keywords: prostatitis; periodontal disease; bleeding index; PSA; oral-systemic health